2021
DOI: 10.1177/08982643211032483
|View full text |Cite
|
Sign up to set email alerts
|

Self-Reported Behavior Change and Predictors of Engagement With a Multidomain Brain Health Intervention for Midlife and Older Adults: A Pilot Clinical Trial

Abstract: Objectives This study evaluated the efficacy of a multidomain brain health intervention on health behavior change and sought to understand whether health literacy or brain health knowledge predicted engagement with the intervention. Methods One-hundred thirty midlife and older adults were assigned to one of three intervention conditions: brain fitness (B-Fit) utilizing education and goal setting, education-only, or waitlist. Questionnaires were completed at baseline and post-intervention. Results Both B-Fit an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 36 publications
0
2
1
Order By: Relevance
“…Despite this change, both cohorts were provided with the same educational information that focused on the same eight topics. No meaningful cohort differences were found in data from this study nor in Boyd and colleagues study [10] .…”
Section: Participantscontrasting
confidence: 67%
See 2 more Smart Citations
“…Despite this change, both cohorts were provided with the same educational information that focused on the same eight topics. No meaningful cohort differences were found in data from this study nor in Boyd and colleagues study [10] .…”
Section: Participantscontrasting
confidence: 67%
“…In prior work with a pilot multidomain intervention, called B-Fit (Brain Fitness), we found that, unlike waitlist controls, the B-Fit and education-only conditions self-reported engaging in significantly more healthy brain aging behaviors post-training. Furthermore, compared to waitlist controls, B-Fit participants self-reported significantly higher post-training engagement in positive health behaviors [10] . In the current study, we focused on whether behavior change was sustained at one-year and any cognitive benefits associated with the intervention.…”
Section: Results From Prior Multidomain Studiesmentioning
confidence: 88%
See 1 more Smart Citation